2020
DOI: 10.1002/ceat.202000104
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Removal of Ammonia by Hierarchically Porous Carbons from a CO2 Capture Process

Abstract: The amine‐based post‐combustion carbon capture process is one of the most efficient methods for treating large‐scale CO2, but it produces hazardous products due to chemical transition and degradation of the absorbents. In this study, carbon‐based materials were used as adsorbents for the removal of NH3, and their adsorption capacities, adsorption rates, and stabilities were examined by comparing commercial activated carbon (AC) with hierarchically porous carbon (HPC). HPC‐Step4 possessed a higher number of tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…This self-activation process mitigates the needs for incorporating conventional activators that are often highly corrosive and toxic. These exceptional properties make SA a promising option for fabricating porous carbons for adsorption-related applications. Notably, Hu et al demonstrated nitrogen-doped carbon with hierarchical pores from SA pyrolysis, achieving excellent CO 2 capture performance (4.57 mmol g –1 ). However, the use of highly corrosive acid mixtures of H 3 PO 4 and HNO 3 raises serious environmental and safety concerns.…”
Section: Introductionmentioning
confidence: 99%
“…This self-activation process mitigates the needs for incorporating conventional activators that are often highly corrosive and toxic. These exceptional properties make SA a promising option for fabricating porous carbons for adsorption-related applications. Notably, Hu et al demonstrated nitrogen-doped carbon with hierarchical pores from SA pyrolysis, achieving excellent CO 2 capture performance (4.57 mmol g –1 ). However, the use of highly corrosive acid mixtures of H 3 PO 4 and HNO 3 raises serious environmental and safety concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Although the high removal efficiency of NH 3 can be achieved, they may still suffer possible problems such as temperature/pressure requirements, high processing costs, and the generation of harmful byproducts. By comparison, the adsorption of NH 3 over porous materials is one of the most simple and efficient methods to remove the odorous gas (Zheng et al, 2016;Choi et al, 2020;Mirzaie et al, 2021), and carbon materials always draw a lot of attention owing to their high surface area, rich pores, adjustable structure and low cost Kamran and Park 2021b). The physical and chemical activization of carbon materials may further increase their adsorption capacity through the enriched pore structure and active functional groups Kamran and Park 2021a;Kamran and Park 2021b;Kamran et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Energy-efficient adsorption separation has received intensive attention in NH 3 capture in the past few decades, which promotes the development of many functional adsorbents. Thus, not only traditional adsorbents like porous carbons, mesoporous silica, and zeolites but also novel porous materials such as metal–organic frameworks (MOFs), covalent organic frameworks (COFs), and hydrogen organic frameworks (HOFs) ,, have been used for NH 3 capture. In general, there are two main challenges in NH 3 capture by solid porous adsorbents.…”
Section: Introductionmentioning
confidence: 99%